Développer puis réduire les expressions suivantes.
A = 3(x-2)
B = -4(2x + 1)
C = -5x (-x + 2)
D = (3x - 2)²
E = (4x + 1)²
F = ( x + 3)( x - 1)
G = (2x - 1)(2x + 1)
H = (3x - 5)(-2x + 1)
I = 3(x - 2)( x + 5)
K = -2(x + 3)(2x-4)
L = 4(x - 3)²
M = ( x + 1)²-( 2x + 3)( x - 5)

1

Réponses

  • Utilisateur Brainly
2014-08-27T15:56:33+02:00
A = 3(x-2)
A= 3x - 6

B = -4(2x + 1)
B= - 8x - 4

C = -5x (-x + 2)
C= 5x² - 10x

D = (3x - 2)²
D= 9x² - 12x + 4

E = (4x + 1)²
E= 16x² + 8x + 1

F = ( x + 3)( x - 1)
F= x² - x + 3x - 3
F= x² + 2x - 3

G = (2x - 1)(2x + 1)
G= 4x² - 1

H = (3x - 5)(-2x + 1)
H= -6x² + 3x + 10x - 5
H= - 6x² + 13x - 5

I = 3(x - 2)( x + 5)
I= (3x - 6)(x + 5)
I= 3x² + 15x - 6x - 30
I= 3x² + 9x - 30

K = -2(x + 3)(2x-4)
K= (- 2x - 6)(2x - 4)
K= - 4x² + 8x - 12x + 24
K= - 4x² - 4x + 24

L = 4(x - 3)²
L= 4(x² - 6x + 9)
L= 4x² - 24x + 36

M = ( x + 1)²-( 2x + 3)( x - 5)
M= x² + 2x + 1 - (2x² - 10x + 3x - 15)
M= x² + 2x + 1 - 2x² + 10x - 3x + 15
M= - x² + 9x + 16